A study on macroeconomic determinants towards Bursa Malaysia Stock Index / Siti Nur Hajar Abdul Hamid - Abdul Hamid, Siti Nur Hajar (2010)
The research is about a study on the macroeconomic variables towards Bursa Malaysia stock index. The scope of the study only focuses on the price movement of the FTSE Bursa Malaysia KLCI as a result of the changing in consumer price index, exchange rate, money supply and industrial production index. The objective of this study is to determine the relationship between the macroeconomic variables with the price movement of Bursa Malaysia Stock Index. There are four macroeconomic variables that have been chosen in this study, namely, consumer price index, exchange rate, money supply and industrial production index. The data period cover from January 2000 to December 2009 (10 years), retrieved from Bank Negara and Bursa Malaysia. The Multiple Linear Regression Model is use to investigate the relationship between macroeconomic variables with the price movement of Bursa Malaysia Stock Index by using E-views Software. Three of the macroeconomic variables except industrial production index shows significance correlation and are able to affect the price movement of FTSE Bursa Malaysia KLCI. The final findings indicate that consumer price index and exchange rate show negative significant, money supply shows a positive significant and industrial production index has no relationship with the price movement of FTSE Bursa Malaysia KLCI.